Augmenting Supply Chain Practices through Human Resource Management: An Analytical Framework in Indonesian Perspective - Alam, Heldy Vanni; Syarifudin, M. Apun (International Journal of Supply Chain Management, 2018)
The aim of the present study is to empirically investigate the association between the supply chain rehearses and its augmentation with the human resource management practices from the context of Indonesia.  For this purpose, a conceptual model is developed based on the various items of HRM and SCM while taking implementation and outcome as subfactors for the SCM augmentation. A sample of 236 respondents has been considered based on the various industry experts, dealing with 50 business firms in the region. Empirical findings explain the fact that both factors of SCM under the title of implementation and outcome have their significant association with the HRM practices in the region of Indonesia. All the HRM practices are significantly associated with the SCM for growth and augmentation and express positive change. The managerial implication of the study can be viewed in a sense that it provides meaningful guidelines to various industry experts and managers. However, the study also has some limitations which are limited respondents which should be covered in the coming time. The value of the study can be viewed in a sense that it is covering the gap in existing literature while integrating HRM and SCM for the growth and augmentation in the region of Indonesia.